Adolescent Somatic Development of Junior High School Students in Denpasar - Soetjiningsih Soetjiningsih (Indonesian Pediatric Society, 1999)
Junior high school adolescent represents a transition period from child toadult. In this period the growth and development takes place very rapidly. This study intended to understand adolescent somatic development of junior high school students in Denpasar; subjects were 450 students of grades I, II, III from 3 junior high schools in Denpasar selected randomly in February 1998. Anthropometric and blood pressure measurements were performed. The structured questionnaires were given to the parents, which were collected during the anthropometric measurement.Â The results were that only 428 subjects completed their data, consisted of 200 boys and228 girls. At the age of t2 years the average anthropometricÂ measurements were higher in girls, but at the age of 13, 14, IS years, the boys was higher. The average systolic blood pressure was 101.67 mmHg and diastolic was 75.0 mmHg, no significant difference between boys and girls. Based on NCHS standard, it was found that 10 % of boys and 3.5% of girls had body weight below the normal limits, and 5.5% boys and 7.9% girls having body height below the normal limits. The average age of menarche was 12.47 years (range 11 -14 years, SD 0.81). The somatic development or boys and girls of junior high school students which wasÂ investigated followed the normal development sequence. Only small number of adolescent found having body weight and height below the normal limits.